2017
DOI: 10.1097/bor.0000000000000398
|View full text |Cite
|
Sign up to set email alerts
|

Human papilloma virus and lupus: the virus, the vaccine and the disease

Abstract: We review clinical, epidemiological and molecular data suggesting involvement of HPV infection in the pathogenesis of SLE. We suggest that these findings may justify the development of new HPV vaccines containing viral peptides that bear no homology to the human proteome, in order to avoid possible adverse immune cross-reactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 112 publications
0
18
0
1
Order By: Relevance
“…Molecular mimicry is one mechanism implicated in the break of tolerance. A recent study identified a penta-peptide (SKVVS) in the human papillomavirus (HPV) protein L1 that is shared with KIR2DL1, 2DL2, 3DL1, 3DL2, and 2DL4 and suggested that HPV infection in genetically predisposed individuals may contribute to lupus via molecular mimicry (38, 39). In this light, it would be interesting to study whether the presence of anti-KIR autoantibodies correlates with HPV infection, but the lack of these data in our cohort preclude such analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular mimicry is one mechanism implicated in the break of tolerance. A recent study identified a penta-peptide (SKVVS) in the human papillomavirus (HPV) protein L1 that is shared with KIR2DL1, 2DL2, 3DL1, 3DL2, and 2DL4 and suggested that HPV infection in genetically predisposed individuals may contribute to lupus via molecular mimicry (38, 39). In this light, it would be interesting to study whether the presence of anti-KIR autoantibodies correlates with HPV infection, but the lack of these data in our cohort preclude such analyses.…”
Section: Discussionmentioning
confidence: 99%
“…However, the fact that the effect of anti-KIR-containing IgG was observed on isolated NK cells, that IgG had opposite effects in educated and tolerized subsets of NK cells and that NK cells retuned following wash-out of IgG strongly suggest that the effect on NK cells were at least in part the result of antibody-mediated blockade of KIR/KIR-ligand interactions. This speculation is not unlikely given the clear data on the effect on NK cells that are triggered upon exposure to the anti-KIR2D antibody lirilumab (39).…”
Section: Discussionmentioning
confidence: 99%
“…TLR4 signaling was increased with transgenic mice for a TLR chaperone molecule (gp96), which resulted in a lupus-like autoimmune glomerulonephritis 26 . Flares of autoimmune diseases have been observed with infection 82 in humans and also is an inducer of autoimmunity in mice. Decreased anti-dsDNA antibodies were observed in TLR2 and TLR4 knockout C57BL/6 (lpr/lpr) mice; and autoantibodies were induced by LPS stimulation through the TLR4-dependent cell signaling pathway in lupus-prone mice 83 , 84 .…”
Section: Discussionmentioning
confidence: 99%
“…This has included high-profile coverage of individuals who died after HPV vaccination. 88,89 The main concerns raised about the safety of HPV vaccination have focused on death following vaccination, 88,89 autoimmune and neurological conditions, [90][91][92][93][94][95][96][97][98] and premature ovarian insufficiency (POI) or ovarian failure. [99][100][101][102][103][104][105] Addressing myth 3…”
Section: Mythmentioning
confidence: 99%